2022
DOI: 10.1021/acsestwater.2c00008
|View full text |Cite
|
Sign up to set email alerts
|

Surface Microlenses for Much More Efficient Photodegradation in Water Treatment

Abstract: The global need for clean water requires sustainable technology for purifying contaminated water. Highly efficient solar-driven photodegradation is a sustainable strategy for wastewater treatment. In this work, we demonstrate that the photodegradation efficiency of micropollutants in water can be improved by ∼2–24 times by leveraging polymeric microlenses (MLs). These microlenses (MLs) are fabricated from the in situ polymerization of surface nanodroplets. We found that photodegradation efficiency (η) in water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…A higher concentration of active species in the MLs-induced system is confirmed by ESR characterization in our previous work. 57 Similar to the photolysis system without catalysis, the ESR spectra in Figure 5 suggested that the photodegradation with ZnO as the catalyst could also be accelerated, due to the larger amount of free radicals from the focusing effect of surface MLs.…”
Section: Free Radicals From Mlsmentioning
confidence: 79%
See 2 more Smart Citations
“…A higher concentration of active species in the MLs-induced system is confirmed by ESR characterization in our previous work. 57 Similar to the photolysis system without catalysis, the ESR spectra in Figure 5 suggested that the photodegradation with ZnO as the catalyst could also be accelerated, due to the larger amount of free radicals from the focusing effect of surface MLs.…”
Section: Free Radicals From Mlsmentioning
confidence: 79%
“…61 The condition used to fabricate the random surface MLs was the optimized one in our previous work. 57 After the standard solvent exchange process, the chamber filled with liquid was sealed and horizontally set under UV light (365 nm, Analytik Jena UV lamp) for 15 min. Surface ML arrays (MLAs) in the photodegradation processes were fabricated with lauryl methacrylate (LMA, Acros Organics) as the monomer in solution A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is considerable interest in sustainable new technologies that avoid disinfection byproducts. Two conventional alternatives, ozonation and UV radiation, have their own limitations. While little to no harm to humans and aquatic life is caused by UV-radiation-based processes, they are less cost-effective than chlorination . Alternatively, bacteria and viruses are more effectively destroyed by ozone.…”
Section: Introductionmentioning
confidence: 99%
“…24−26 While little to no harm to humans and aquatic life is caused by UV-radiation-based processes, they are less cost-effective than chlorination. 27 Alternatively, bacteria and viruses are more effectively destroyed by ozone. Still, ozonation is not cost-effective for the treatment of water with substantial amounts of particulate matter or total organic carbon, as well as high biochemical or chemical oxygen demand.…”
Section: Introductionmentioning
confidence: 99%